2017
DOI: 10.1097/md.0000000000007294
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Implantable Collamer Lens Visian ICL V4 and ICL V4c for high myopia

Abstract: The aim of this study was to investigate the visual quality of the 2 kinds of intraocular lens: Visian implantable collamer lens (ICL) V4 and Visian ICL V4c implantations for high myopia.Twenty cases (20 eyes) with high myopia who received Visian ICL V4 implantation and 18 cases (18 eyes) with high myopia who received Visian ICL V4c implantation in our hospital from April 1, 2014 to November 31, 2016 were enrolled. In 1-month follow-up, near vision, best corrected distant visual acuity (BCVA), uncorrected dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 24 publications
(24 reference statements)
0
21
0
1
Order By: Relevance
“…The outcomes demonstrated that the quality of vision and patient satisfaction is better with ICL than with femtosecond-LASIK. Tian Y [37] and Hyun J [38] compared the differences in visual and refractive results between ICL-V4 and ICL-V4c. Both authors found that the central hole did not significantly affect the visual and refractive outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes demonstrated that the quality of vision and patient satisfaction is better with ICL than with femtosecond-LASIK. Tian Y [37] and Hyun J [38] compared the differences in visual and refractive results between ICL-V4 and ICL-V4c. Both authors found that the central hole did not significantly affect the visual and refractive outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Both the conventional ICL and the ICL V4c implantation procedures provide good optical and visual quality [ 16 , 19 , 24 , 26 28 ]. Tian et al found that the two kinds of ICL had similar efficacy of visual quality for high myopia, and also similar results in low-order aberrations, while high-order aberrations and spherical aberrations were higher after ICL V4c implantation [ 28 ]. In Kamiya’s study, the two ICLs produced similar optical quality and intraocular scattering results [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 2 kinds of ICLs were reported to have similar efficacy on visual quality for high myopia. [8] Usually, much more attention has been paid to cataract formation and secondary glaucoma after the ICL implantation. [9] Less study has reported on the accommodative function after ICL implantation.…”
Section: Introductionmentioning
confidence: 99%